Pengaruh Inflasi, Jumlah Uang Beredar, Dan BI Rate Terhadap Pertumbuhan Ekonomi Indonesia Tahun 2020-2023 - Putri Br Jawak, Anastasia Yolanda; Sipayung, Silviana Megawati (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to determine the effect of inflation, money supply and bi rate on Indonesia's economic growth in 2020-2023. The type and source of research data used is secondary data, which is obtained directly from the object under study. Data processing uses SPSS 23.0. The analytical method used is multiple linear regression. With linear regression coefficients, the research results show that inflation has a significant negative effect on economic growth. This can be stated by looking at the magnitude of the inflation coefficient which is -5.141. From these results it can be concluded that if inflation rises then economic growth will decrease. JUB has a significant negative effect on economic growth. This can be stated by looking at the magnitude -6,220. From these results it can be concluded that if JUB increases then economic growth will decrease and interest rates have a significant negative effect on economic growth. This can be stated by looking at the magnitude -4.246. So it can be concluded that if interest rates rise then economic growth will decrease.